Enhancing spectrum efficiently and energy efficiently via offloading mechanism in heterogeneous networks (in context of Wi-Fi and LTE-Advanced) - Saleh, Nafeesa; Patel, Niteen (2017 International Conference on Innovations in Electronics, Signal Processing and Communication (IESC), 2017)
Due to recent increase in wireless mobile users and data usage, the available spectrum is limited and there is need to device new methods. Offloading of user traffic from macro tier to small cell tiers is the concept of Heterogeneous Networks (HetNets) but this lead to problems like densification of cellular structure, interference in various tiers, complexity and cost. The key contribution of this paper includes enhancing Spectrum Efficiency (SE) and Energy Efficiency (EE) via biased Intra or Inter RAT offloading. This is done by formulating a multi-objective optimization problem in which both SE and EE are maximized subject to constraints of minimum attainable throughput in both Radio Access Technologies and genetic algorithm is used to solve this problem. Moreover, the channel modeling is in accordance with standard 3GPP specifications which capture the expectation of real scenario in our objective function. The impact on this finding will be enhancement of user's data rate and QoS.